Incorporating Field Experience into International Agricultural Development Programs - Alexis Zickafoose; Gary Wingenbach (MDPI AG, 2023)
Some graduate education programs support experiential learning but do not require practical experiences for students specializing in international agriculture development. We examined U.S. land grant university graduate international agricultural education program descriptions for experiential learning requirements and found them lacking. The literature surrounding volunteerism is reviewed and examples are described. International volunteerism can fill the experience gap for future international agricultural development professionals studying at U.S. land grant institutions. Graduate students can acquire practical field experiences through short- or long-term volunteer assignments, such as those in the USAID Farmer-to-Farmer volunteer program for international agriculture development. Graduate students build their capacities by providing technical and agricultural assistance in Farmer-to-Farmer assignments, whereas host country participants enhance their knowledge, skills, and abilities to expand and increase agricultural sector productivity. Short-term international volunteer assignments help graduate students gain practical experience, improve interpersonal skills, and enhance cultural competencies. Host communities and volunteers alike benefit by engaging in intercultural exchanges that promote increased understanding of differing societies worldwide.